Monitoring Study of The Seagrass Ecosystem in Panrangluhu Beach Marine Water, Bulukumba, South Sulawesi - Supardi, Wahyu; Pradana, Andi Rizki Adi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The lamu meadow ecosystem is spread across Panrangluhu Beach, Bulukumba Regency. This research aims to identify seagrass types, density levels and seagrass cover in the Marine Waters of Panrangluhu Beach, Bulukumba Regency. The method used is a survey method by directly observing the condition of the seagrass ecosystem. Observations of seagrass beds used quadrant transects measuring 50 x 50 cm, along a 50 meter transect line with three transect lines. The research results obtained in the sea waters of Panrangluhu Beach were E. acroides at 81.75 stands/m2, T. hemprichii seagrass at 31.5 stands/m2, and S. isotifolium seagrass had a density value of 28.5 stands/m2. The seagrass density condition is classified as dense density, with dense seagrass cover conditions. The quality of the marine water environment at Panrangluhu Beach still supports seagrass life.